Results of experimental studies of a jet-reactive turbine: Effect of pressure on rotation speed - Baha, Tetiana; Vaneev, Serhii; Pavlenko, Ivan (DataverseUA, 2025)
This data contains the results of experimental studies on a jet-reactive turbine to investigate the effect of pressure on its rotational speed.